P45. Reduction in motor unit number index (MUNIX) in the course of ALS in relation to the D50 ALS disease progression model. Issue 8 (August 2018) - Rödiger, A.; Gaur, N.; Hohmann, M.; Appelfeller, M.; Tümmler, A.; Ringer, T.M.; Gunkel, A.; Stubendorff, B.; Axer, H.; Witte, O.W.; Grosskreutz, J.
Abstract : Introduction: Motor unit number index (MUNIX) is a fast new technique, relying on surface interference patterns (SIP) recorded during voluntary isometric contractions. Recent studies demonstrated already a decline of motor unit index values in pre-symptomatic muscles of ALS patients and during disease progression. To quantitatively describe individual ALS disease progression and to compare different disease courses, we have recently introduced the D50 ALS disease progression model. Its advantage is a significant noise reduction of ALSFRS-R and the ability to relate any event with the calculated disease burden and disease covered. Objective: Our aim was to analyze MUNIX of four different muscles in the context of the D50 disease model and determine the extent of damage in relation to time and disease aggressiveness. Methods: MUNIX-measurement were performed prospectively in 135 ALS patients, 20 ALS-mimics and 16 healthy controls, cross-sectional in up to four muscles (APB, ADM, TA, EDB) in our neuromuscular unit by trained raters. In addition, in a patient subset repeated measurements during disease progression were performed as well and quality parameters were obtained. The D50 ALS disease progression model is based on a sigmoidal decay function to describe the transition of the ALSFRS-R from full health to maximum disease. The model includes three parameters: D50 = time taken for ALSFRS-R to drop to 24, dx = slope of ALSFRS-R decrease, relative D50 (rD50) = calculated value describing individual disease covered in reference to D50. Results: MUNIX values were significantly reduced in ALS patients versus controls (APB 64, 5 ± 48, 1 [mean ± SD] vs. 153, 7 ± 61, 2; ADM 62, 3 ± 45, 8 vs. 132, 9 ± 30, 7; EDB 38, 5 ± 30, 2 vs. 87, 3 ± 44, 7 and TA 67, 5 ± 36, 5 vs. 122, 8 ± 39, 2) and showed marked variability. MUNIX was also reduced in ALS patients compared to ALS-mimics. Low MUNIX value in ADM correlated with a low ALSFRS-R score. MUNIX values of APB were reduced in phase I already and did not change in phase II and III/IV, EDB, ADM and TA dropped in phase II. ALS progression types (fast, intermediate, slow progressors) correlated with APB MUNIX reduction. Conclusion: Decreased MUNIX values can be detected in all muscles in early phase of ALS disease, especially in APB, independently of ALSFRS-R-subscores and clinical signs. The D50 model allows comparing different progression types; hence we were able to show that the early APB reduction correlates with disease aggressiveness and can be a marker for ALS patients with fast progression. Acknowledgment: This research is supported byBMBF (Bundesministerium für Bildung and Forschung) in the framework of the E-RARE programme (PYRAMID) andJPND (OnWebDuals) and theDt. Gesellschaft für Muskelkranke (DGM).